The development of an instructional decisions test for secondary mathematics teachers - Baldeviso, Evelyn V. 1947- (University of the Philippines Diliman, 1975)
An Instructional Decision Test which consists of fifteen exercises in an objective-strategy sequence was designed in this study to assess a teacher behavior-- that of identifying and selecting strategies best suited to attain specific objectives. This Instructional Decisions Test is recommended for methods courses in teacher training institutions as a basis of information on pre-service teacher performance.